Rate control algorithm for no-feedback distributed video coding - HENJian C; Chao HUI; Yong-hong KUO (Tongxin xuebao)
In order to address the high requirement of accuracy on rate estimation in the existed bit-plane-level encoder rate control (ERC) methods, a frame-level ERC algorithm was proposed. It used hierarchical fast motion compensated interpolation to obtain high quality side information estimation at the encoder, and removed the difference between bit-planes with cyclic shift to make the coding rates on each bit-plane homogeneous, therefore achieving a frame-level rate control. The simulation results show that compared with the existed methods, the proposed algorithm can improve the quality of side information estimation considerably especially for the middle-high motion video sequences and in-crease the average PSNR (peak signal-to-noise ratio) of decoded video.